IFRS adoption challenges in developing economies: an Indian perspective. Issue 4 (4th April 2017) - Sharma, Sharad; Joshi, Mahesh; Kansal, Monika
Abstract : Purpose: This study aims to examine the perceptions of accounting practitioners and users about implementation challenges with International Financial Reporting Standards (IFRSs) at the pre-implementation stage. Under institutional pressures, India conveyed its decision to implement IFRS beginning 1 April 2016, despite initial reluctance to adopt IFRS. It specifically explores the responses of accounting professionals (preparers) and the banking industry professionals (users) in India to challenges in IFRS implementation, rather than more widely researched dimensions of IFRS implementation such as reasons for adoption, experience effects and diversity in practice. Design/methodology/approach: A quantitative research approach was adopted, using a questionnaire survey that provided 192 responses from accounting practitioners and banking professionals working in India. Findings: The findings convey IFRS implementation preparedness perceptions of participants with respect to education, training and information technology (IT) infrastructure. Respondents acknowledged the efforts and capability of the accounting body, the Institute of Chartered Accountants of India, but expressed reservations about training, cost, interpretation, IT infrastructure and staffing. The accounting practitioners and the users have similar perspectives on the subject of awareness and preparedness challenges of IFRS implementation. Practical implications: The study heightens awareness of the challenges facing jurisdictions who express initial reluctance, although they ultimately decide to adopt IFRS on account of institutional pressures. The analysis suggests that the International Accounting Standards Board should increase focus on implementation issues, in addition to updating and making IFRSs. Originality/value: The study is distinct from the studies in abundance on the creation of accounting standards, implementation benefits and their implication in a specific geography.